Post-operative retention of urine after general and spinal anesthesia in general surgical patients - Karki, Om Bahadur (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: Post-operative urinary retention (POUR) is an underestimated troublesome condition following surgery in which a patient cannot urinate even when the bladder is completely filled. with consequences like bladder dysfunction, urinary tract infection, and catheter-related complications. It is important to be aware and to identify patients at risk of developing POUR. The aim of the study was to determine the incidence and risk factors of POUR in general surgery patients. Methods: We conducted a prospective cohort study among 487 patients from January 2024 to April 2025. Ethical approval was obtained from the institutional review committee. Consecutive sampling method was used. The categorical variables were presented as frequencies, and were compared using the chi-squared test. Continuous variables were compared using the student’s t test. P-value of <0.05 was considered statistically significant. Results: Total 487 patients were included in the study, of which 82 patients (63 males and 19 females) developed POUR with an overall incidence of 16.83%. Mean urine output was 563.7 ml. The mean age of POUR patients was significantly higher than for non-POUR patients (52.5±15.65 years vs. 47.8±14.55 years, p=0.0087). males (p=0.004), diabetes (p=0.0016), spinal anesthesia(p<0.001) were significant risk factors for the development of POUR. Conclusions: The incidence of POUR is higher in males, elderly patients, diabetes and patients undergoing surgery under spinal anesthesia.